Resistance of mice to infection with secondary hydatid disease by polyamine oxidase isomer - Wathba ُEdrees Tohala (College of Education for Pure Sciences, 2013)
ABSTRACT Polyamine oxidase activity in cerebrospinal fluid of normal children was determined. The specific activity of crude PAO was found 64.16  8.18 enzyme unit/mg protein. Two main peaks of high PAO activities were obtained I and II with specific activity of 1201.9 and 1157.2 enzyme unit/mg protein, and with purification folds of 18.2 and 17.5 respectively. The resistance to infection with secondary hydatid disease was studied in mice activated by partially purified CSF-PAO with spermine and infected with protoscoleces of Echinococcus granulosus. The results revealed an obvious decrease in numbers, weights and diameters of secondary hydatid cysts grown, and elevation in the percentage of reduction of hydatid cysts, and a decrease in liver and spleen weights and their organ indices, in mice activated by different concentrations of PAO II 200-1000 µg/ 10 gm body weight with constant concentration 200 µg Spm throughout one month, and with optimum concentration 800 µg/ 10 gm body weight PAO II with 200 µg Spm throughout two and three months, in comparison with positive and negative control groups. Therefore, it was concluded that PAO II isolated from CSF with Spm could be considered as an effective resistance against infection with secondary hydatid disease.